ANALISIS PENGARUH STRUKTUR KEPEMILIKAN TERHADAP KINERJA PERUSAHAAN MANUFAKTUR - Penta Indarwati (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2015)
This study aims to examines the effect of ownership structure on corporateperformance of manufacturing companies listed in BEI or Indonesia StockExchange for the period 2010-2013. Ownership structure consisted offoreign ownership, government ownership, managerial ownership,institutional ownership and family ownership. Corporate performance ismeasured by ROE (Return on Equity). This study is used 216 samples ofmanufacturing companies listed in BEI or Indonesia Stock Exchange forthe period 2010-2013. This study is used a multiple regression. The resultsshow that foreign ownership, government ownership, institusionalownership and family ownership have a positive and significant effect toCorporate performance. Managerial ownershiphas no influenceonCorporate performance.